Bill Atkin: Colleague, Mentor, Teacher, Friend - Angelo, AH; McLay, Geoff; Marten, Bevan (Victoria University of Wellington Law Review, 2015)
The three authors, all academics at Victoria University of Wellington Faculty of Law, provide their respective tributes to Professor Bill Atkin in his various roles. Professor Tony Angelo provides his account of Professor Atkin as a colleague and friend since the 1970s. Professir Geoff McLay speaks of his experience learning tort law in the 1980s under Professor Atkin, and eventually becoming his colleague. Bevan Marten discusses Professor Atkin's lectures in the early 2000s, as well as his mentorship and eventual status as colleagues.